PENGARUH PENGGUNAAN MODEL SNOWBALL THROWING TERHADAP HASIL BELAJAR PKn KELAS V DI SEKOLAH DASAR - Jalil, Abdul; Utami, Sri; Salimi, Asmayani (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe problem of the present study â€œhow is the effect of the implementation of snowball throwing model on fifth grade studentsâ€™ gain score of Civic subject at SDN 34 Pontianak Selatan?â€. The present study aims at analyzing the effect of snowball throwing implementation on studentsâ€™ gain score of civic subject learning. The study employs quasi experiment method. The population of the study is the 157 fifth grade students of SDN 34 Pontianak Selatan year 2016/2017. The sample of the study is students of VD (experiment class) and V E (control class). The data is collected through studentsâ€™ gain score test in the form of multiple choice with 30 item test which has already tested (validity and reliability). The result of the study indicates the average gain score (posttest) is of the control class and experiment class are 77,70 and 85,77, respectively. According to the t-test, the significance = 0,019 < Î± 0,05. In conclusion the implementation of snowball throwing effects to the fifth grade studentsâ€™ gain score of civic subject learning. According to the effect size calculation it obtains = 0,482 which means that the implementation of snowball throwing provide average effect on the studentsâ€™ gain score.Key words: Effect, Snowball Throwing, Gain Score, CivicÂ